Power struggles: A sociological approach to activist communication - Wolf, Katharina (Elsevier, 2018)
This paper proposes an alternative approach to the scholarship of activist public relations, based on the ideas of the sociologist Pierre Bourdieu; notably his understanding of activism in society. Although Bourdieu is one of the most quoted sociologists in the world (Santoro, 2011; Truong & Weill, 2012), his work has only received limited attention in public relations, and has been entirely ignored within the context of activist communication. This is despite his focus on power, relationships and the role of activists in modern democracies, all of which are central themes in public relations practice and research. Based on Bourdieu’s theory of practice, the discipline’s prevailing, dominant, industry serving, functionalist paradigm positions public relations’ role in society as to perpetuate social inequalities. However, drawing on his ideas leads us to question if public relations skills could be equally utilized to challenge existing power imbalances in society, either in support or on behalf of those groups and individuals whose voices have been drowned out by traditional public relations efforts. The author argues that Bourdieu was not only an accomplished scholar, but also an activist in his own right. It is this combination of personal experience with academic ideas that lends weight to his scholarly work through which he urged the scholarly community to utilize their skills, knowledge and research to challenge (perceived) inequalities in society. The emergence of this type of activist academic, committed to giving voice to multiple coexisting, sometimes directly competing points of views, would arguably further justify and strengthen the existence of public relations as a scholarly discipline in its own right.